2005
DOI: 10.1530/eje.1.01848
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone does not adversely affect fibrinogen or tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1) levels in 46 men with chronic stable angina

Abstract: Objective: In women, sex hormones cause increased morbidity and mortality in patients with coronary heart disease (CHD) and adversely affect the coagulation profile. We have studied the effect of physiological testosterone replacement therapy in men on coagulation factor expression, to determine if there is an increased risk of thrombosis. Methods: Double-blind, randomized, placebo-controlled trial of testosterone in 46 men with chronic stable angina. Measurements of free, total and bioavailable testosterone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…However, testosterone does not adversely affect blood coagulation status. (38) In the present study we have observed lower clotting time in males than females.…”
Section: Discussionsupporting
confidence: 54%
“…However, testosterone does not adversely affect blood coagulation status. (38) In the present study we have observed lower clotting time in males than females.…”
Section: Discussionsupporting
confidence: 54%
“…There is a positive correlation with tissue plasminogen activator (tPA) which is one of the major fi brinolytic agents (Glueck et al 1993). Interventional trials have shown a neutral effect of physiological testosterone replacement on the major clotting factors (Smith et al 2005) but supraphysiological androgen administration can produce a temporary mild pro-coagulant effect (Anderson et al 1995).…”
Section: Figurementioning
confidence: 99%
“…Physiological testosterone replacement has been reported in a number of trials to improve lipid profiles, increase insulin sensitivity, and reduce visceral fat, clotting and inflammatory profiles (reviewed in (7)(8)(9)). Importantly, no adverse effects of testosterone replacement therapy on coagulation have been demonstrated in men with chronic stable angina (10). Furthermore, animal studies have shown that testosterone replacement inhibits the development and progression of atheroma (11).…”
Section: Introductionmentioning
confidence: 99%